Preparation method of lead paste and negative electrode of lead-acid battery negative electrode of bamboo-based hard carbon material
Patent Information
- Application Number
- CN202611002953.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-07
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2046-07-07
AI Technical Summary
[0003]而铅酸蓄电池负极过低的活性物质利用率严重阻碍了负极活性物质轻量化降成本技术的发展与应用,即使大幅度降低负极铅膏的视密度,增加铅膏含酸量
本发明中的竹基硬碳材料的铅酸蓄电池负极配方,包括铅粉、竹基硬碳材料、磺酸海藻酸钠竹粉、硫酸钡、腐殖酸、木素磺酸钠、复合短纤维、稀硫酸和纯水;
Smart Images

Figure CN122511853B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of lead-acid battery technology, specifically to a lead paste for the negative electrode of a lead-acid battery made of bamboo-based hard carbon material and a method for preparing the negative electrode. Background Technology
[0002] Lead-acid batteries serve as the power source for electrical equipment, providing power for its normal operation. They can also act as backup power, maintaining system operation when the main power supply fails. The excellent cost-effectiveness, large capacity, and mature technology of lead-acid batteries have made them stand out among various battery types, and they currently account for more than half of the battery market. In recent years, with the rapid development of the electronics and information industry and the even more rapid growth of the power and communication sectors, lead-acid batteries have been widely used in these fields.
[0003] The extremely low utilization rate of active materials in the negative electrode of lead-acid batteries severely hinders the development and application of technologies for lightweighting and reducing costs of negative electrode active materials. Even with a significant reduction in the apparent density of the negative electrode lead paste and an increase in its acid content, while the utilization rate of the active materials in the negative electrode can be significantly improved, the substantial decrease in the apparent density of the negative electrode lead paste will seriously affect the cycle life of the negative electrode active materials. Furthermore, reducing the apparent density of the negative electrode lead paste by increasing its acid content will result in excessive hardness of the lead paste, causing severe grid deformation during application, and placing high demands on the process and equipment. Summary of the Invention
[0004] The technical problem to be solved by the present invention is to provide a negative electrode formulation for lead-acid batteries made of bamboo-based hard carbon material and its preparation method.
[0005] The present invention proposes a technical solution to solve the above-mentioned technical problems: a negative electrode formula for a lead-acid battery made of bamboo-based hard carbon material, comprising the following raw materials in parts by weight: 100 parts of lead powder, 0.2-1.5 parts of bamboo-based hard carbon material, 0.2-0.8 parts of bamboo powder containing sodium alginate sulfonate, 0.5-1.2 parts of barium sulfate, 0.2-0.8 parts of humic acid, 0.1-0.5 parts of sodium lignin sulfonate, 0.05-0.15 parts of composite short fiber, 8-12 parts of dilute sulfuric acid with a density of 1.05-1.20 g / cm³, and 10-15 parts of pure water.
[0006] Preferably, the sodium alginate sulfonate bamboo powder is prepared by reacting a sulfonate-based aniline copolymer with polyaldehyde sodium alginate, and then reacting it with activated bamboo powder.
[0007] Preferably, the composite short fiber is prepared by melt spinning oxazoline polydimethylsiloxane and polyethylene terephthalate.
[0008] Preferably, the oxazoline polydimethylsiloxane is prepared by reacting N,N-dimethyl-2-oxazoline with an epoxy-terminated and carboxyl-terminated polydimethylsiloxane.
[0009] Preferably, the preparation method of the lead-acid battery negative electrode formulation of the bamboo-based hard carbon material includes the following specific steps: S1. Mix sodium hydroxide, sodium sulfate, and deionized water in a mass ratio of 1:2:150. After stirring evenly, add bamboo powder at a mass ratio of 100-120 times that of sodium hydroxide. Stir evenly, heat the mixture in a water bath to 30-32°C, keep it at that temperature for 1-1.5 hours, cool it to room temperature, add hydrogen peroxide at a mass fraction of 30% at a mass ratio of 0.16-0.18 times that of bamboo powder, adjust the pH to 10.5-11.0 with sodium hydroxide, heat the mixture in a water bath to 42-45°C, keep it at that temperature for 1.5-2 hours, transfer it to an ice bath at 0-3°C to terminate the reaction, adjust the pH to 6.5-7.0 with dilute hydrochloric acid, let it stand for 10-20 minutes, wash it 8-10 times with deionized water, filter and dry it, grind it through a 60-80 mesh sieve to obtain activated bamboo powder. The preparation method of S2. sulfonic acid aniline copolymer is as follows: aniline hydrochloric acid solution and ammonium persulfate are mixed at a mass ratio of 4.8~5.2:1, stirred evenly, and then an equal volume of 2,4-diaminobenzenesulfonate acid solution is added. The reaction is continued at room temperature for 24~28 hours. The mixture is washed 8~10 times with deionized water, dried, and ground into powder to obtain sulfonic acid aniline copolymer. S3. Mix sodium polyaldehyde alginate with deionized water at a mass ratio of 0.3~0.5:50, heat to 40~50℃, stir to dissolve, then add 8~10 times the mass of sodium polyaldehyde alginate solution of sulfonic acid aniline copolymer. The sulfonic acid aniline copolymer solution is prepared by mixing sulfonic acid aniline copolymer with 32~36% hydrochloric acid at a mass ratio of 1:50, stirring until homogeneous, and then adjusting the pH to 8.0~9.0 with sodium hydroxide. After stirring until homogeneous, add sulfonic acid aniline copolymer dropwise at a rate of 1~3 ml / min. Add 2-3 times the mass of acetic acid to the sulfonic acid aniline copolymer, adjust the pH to 4.5-5.5 with sodium acetate, heat to 60-62℃, and react for 4-6 hours. Then add 0.4-0.6 times the mass of activated bamboo powder to the sulfonic acid aniline copolymer, stir and keep warm at 100-200 rpm for 2-3 hours, add 20-40 times the mass of anhydrous ethanol to the sulfonic acid aniline copolymer, stir, let stand for 20-30 minutes, filter, wash 3-5 times with anhydrous ethanol, and dry to obtain sodium alginate sulfonate bamboo powder. S4. Mix 4-dimethylaminopyridine, N,N-dimethylglycine, and dichloromethane in a mass ratio of 0.09~0.12:3:400~500, place in an ice bath at 0~3℃, stir until homogeneous, then add dropwise a 6~8% (50~60 times) dichloromethane solution of 2-chloroethyl isocyanate (by mass) of N,N-dimethylglycine at a rate of 1~3 ml / min. Transfer to room temperature and react for 12~14 h. Then add potassium tert-butoxide (3.2~3.5 times) potassium tert-butoxide (by mass) of N,N-dimethylglycine, and continue the reaction for 12~14 h. Extract with dichloromethane, wash with saturated brine, dry with anhydrous magnesium sulfate, and concentrate under reduced pressure to obtain N,N-dimethyl-2-oxazoline. S5. Under a nitrogen atmosphere, epoxy-terminated and carboxyl-terminated polydimethylsiloxane, anhydrous toluene, and tetrabutyl titanate catalyst were mixed in a mass ratio of 10:8:0.01~0.02. The mixture was heated to 110~120℃, and N,N-dimethyl-2-oxazoline was added at 0.2~0.22 times the mass of the epoxy-terminated and carboxyl-terminated polydimethylsiloxane. The mixture was kept at this temperature for 6~8 hours, cooled to 60~62℃, and distilled under reduced pressure. The mixture was precipitated with n-hexane and finally dried to obtain oxazoline polydimethylsiloxane. S6. Oxazoline polydimethylsiloxane, PET and antioxidant 1010 are mixed at a mass ratio of 1:90~100:0.1 and extruded using a twin-screw extruder to obtain extended chain PET; PET, extended chain PET and antioxidant 1010 are mixed at a mass ratio of 500:1~2:0.5 and melt-spun to obtain composite short fibers; S7. By mass fraction, lead powder, bamboo-based hard carbon material, sodium alginate bamboo powder, barium sulfate, humic acid, sodium lignin sulfonate, and composite short fibers are mixed and added into a paste mixer. The mixture is stirred for 8-15 minutes, pure water is added, and stirring is continued for 5-10 minutes. The temperature is raised to 52-58℃, kept at the temperature, and dilute sulfuric acid is added dropwise at a rate of 1-5 ml / min. The temperature is lowered to 40-42℃ by passing cooling water through the mixer, and the density is adjusted to 4.2-4.5 g / cm³ to obtain lead paste. The lead paste is coated onto the grid, heated to 45-50℃, and cured at a relative humidity of 95% for 8-12 hours. Then, the temperature is raised to 60-65℃, and the relative humidity is 50% for 10-15 hours. The mixture is then dried to obtain the lead-acid battery negative electrode formula of bamboo-based hard carbon material.
[0010] Preferably, in step S2 above, the aniline hydrochloric acid solution is prepared by mixing aniline and 1 mol / L hydrochloric acid at a mass ratio of 1.4~1.5:25; the 2,4-diaminobenzenesulfonic acid solution is prepared by mixing 2,4-diaminobenzenesulfonic acid and 1 mol / L hydrochloric acid at a mass ratio of 0.82~0.86:25.
[0011] Preferably, in step S3 above, the preparation method of polyaldehyde sodium alginate is as follows: sodium alginate, deionized water and sodium periodate are mixed in a mass ratio of 1~1.1:5:1.3~1.5, stirred at 60~80 rpm for 8~12 h, the reaction is terminated by adding an equal mass of ethylene glycol to sodium periodate, precipitated with anhydrous ethanol, and then washed with deionized water, filtered and dried to obtain polyaldehyde sodium alginate.
[0012] Preferably, in step S5 above, the preparation method of the epoxy-terminated and carboxyl-terminated polydimethylsiloxane is as follows: Hydrogen-containing silicone oil, anhydrous toluene, 4Å molecular sieve, and Karstedt catalyst are mixed in a mass ratio of 30-50:80:3:0.025, stirred until homogeneous, heated to 70-72°C, and 0.3-0.4 times the mass of the hydrogen-containing silicone oil (16-18% by mass) of an allyl glycidyl ether toluene solution is added. The reaction is maintained at this temperature for 2-3 hours, then cooled to 60-62°C, and 0.24-0.26 times the mass of the hydrogen-containing silicone oil (12-14% by mass) of an allyl glycidyl ether toluene solution is added. A % allyl alcohol toluene solution was heated to 70-72℃ and reacted for 3-4 hours. After cooling, the mixture was quenched with saturated sodium bicarbonate solution, filtered, and rotary evaporated. The mixture was then precipitated with n-hexane and isopropanol in a volume ratio of 3:1. Anhydrous toluene containing 2-2.2 times the mass of hydrosilicone oil and succinic anhydride containing 0.1-0.2 times the mass of hydrosilicone oil were added. Under a nitrogen atmosphere, the mixture was heated to 80-85℃ and refluxed for 4-6 hours. After cooling to room temperature, the mixture was washed with saturated sodium bicarbonate solution, dried with anhydrous sodium sulfate, rotary evaporated, and precipitated again with n-hexane to obtain epoxy-terminated and carboxyl-terminated polydimethylsiloxane.
[0013] Preferably, in step S3 above, the preparation method of polyaldehyde sodium alginate is as follows: sodium alginate, deionized water and sodium periodate are mixed in a mass ratio of 1~1.1:5:1.3~1.5, stirred at 60~80 rpm for 8~12 h, the reaction is terminated by adding an equal mass of ethylene glycol to sodium periodate, precipitated with anhydrous ethanol, and then washed with deionized water, filtered and dried to obtain polyaldehyde sodium alginate.
[0014] Preferably, in step S7 above, the preparation method of bamboo-based hard carbon material is as follows: bamboo powder is mixed with 5% hydrochloric acid at a mass ratio of 1:3, stirred at 80-100 rpm for 2-4 hours, filtered, washed with deionized water 8-10 times and dried to obtain acid-washed bamboo powder; the acid-washed bamboo powder is heated to 500-700℃ at 5-10℃ / min under a nitrogen atmosphere, kept at the temperature for 2-4 hours, pulverized to obtain powder with a median particle size of 2-8μm, the powder is mixed with potassium hydroxide at a mass ratio of 1:2-4, activated at 800-1000℃ for 1-2 hours, washed with deionized water 8-10 times, rinsed with 30-32% nitric acid, dried at 100-110℃, transferred to a plasma treatment instrument, and plasma treated for 3-5 minutes in an oxygen atmosphere at a power of 60-80W, and then transferred to a dryer for drying to obtain bamboo-based hard carbon material.
[0015] Compared with the prior art, the beneficial effects achieved by the present invention are: The lead-acid battery negative electrode formulation of bamboo-based hard carbon material in this invention includes lead powder, bamboo-based hard carbon material, sodium alginate sulfonate bamboo powder, barium sulfate, humic acid, sodium lignin sulfonate, composite short fiber, dilute sulfuric acid and pure water. Sodium alginate bamboo powder is prepared by reacting sulfonic acid aniline copolymer with polyaldehyde sodium alginate, followed by reaction with activated bamboo powder. The Schiff base, sulfonic acid group and sodium alginate introduced on the surface of bamboo powder are added to the negative electrode of lead-acid battery to form a triple anchoring network in lead paste. This effectively inhibits the volume expansion and peeling of active material during charge and discharge, improves cycle life and significantly enhances capacity retention. In the curing and drying stage, it can also react with alkaline components in lead paste to partially transform into insoluble lead alginate gel, further anchoring bamboo powder in the active material skeleton and preventing bamboo powder agglomeration from affecting the uniformity of the negative electrode plate.
[0016] The composite short fiber is prepared by melt spinning oxazoline polydimethylsiloxane and polyethylene terephthalate. Oxazoline polydimethylsiloxane is prepared by reacting N,N-dimethyl-2-oxazoline with epoxy-terminated and carboxyl-terminated polydimethylsiloxane. Introducing oxazoline into the composite short fiber allows it to coordinate and adsorb with the negative electrode active material and form an interfacial interaction with the carboxyl group of sodium alginate. The polydimethylsiloxane segments reduce the surface energy of the fiber, improve the wetting and dispersibility of the lead paste, and significantly enhance the binding force of the negative electrode active material, thereby improving the deep cycle life of the battery. Through the multiple interactions between the composite short fiber and the active material, the overall structural stability is further enhanced. Attached Figure Description
[0017] Figure 1 The discharge voltage-time curves are for Example 1 and Comparative Example 1.
[0018] Figure 2The graph shows the cycle life results for Example 2 and Comparative Examples 1-3. Detailed Implementation
[0019] The present invention will be specifically described below through embodiments. It should be noted that the following embodiments are only used to further illustrate the present invention and should not be construed as limiting the scope of protection of the present invention. Those skilled in the art can make some non-essential improvements and adjustments to the present invention based on the above description. Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those skilled in the art.
[0020] The CAS number of the hydrogen-containing silicone oil in the embodiments and comparative examples of this invention is 63148-57-2, and the CAS number of the allyl glycidyl ether is 106-92-3.
[0021] To more clearly illustrate the method provided by the present invention, the following examples will be used to describe in detail the testing methods for various indicators of the lead-acid battery negative electrode formulations using bamboo-based hard carbon materials prepared in the examples and comparative examples: Batteries assembled from the bamboo-based hard carbon material negative electrode formulations prepared in the examples and comparative examples were subjected to cycle life testing using a 100% DOD full charge-discharge cycle. The specific procedure was as follows: Under a 25±1°C water bath, the battery was discharged at 10A to a termination voltage of 10.50V, then charged at a constant voltage of 14.75V with a maximum current limit (3A), until the current was less than 500mA. It was then charged at 13.80V for 4 hours, constituting one cycle. Cycle life ended when the battery capacity decreased to 70% of its rated capacity. After a full charge under 25°C water bath conditions, the battery was discharged at I20 = 0.15A to 1.75V, and the discharge time t (h) was recorded. The 20-hour rate discharge capacity C was calculated by integrating the current-time curve. 20 And the utilization rate of active substances over 20 hours. Among them, η 20h Rate = C 20 / 6*100%. Example 1
[0022] In this embodiment, the components and weight proportions of the lead-acid battery negative electrode formulation made of bamboo-based hard carbon material are as follows: 100 parts lead powder, 0.2 parts bamboo-based hard carbon material, 0.2 parts sodium alginate sulfonate bamboo powder, 0.5 parts barium sulfate, 0.2 parts humic acid, 0.1 parts sodium lignin sulfonate, 0.05 parts composite short fiber, 8 parts dilute sulfuric acid with a density of 1.05 g / cm³, and 10 parts pure water.
[0023] In this embodiment, the preparation method of the lead-acid battery negative electrode formulation using bamboo-based hard carbon material is as follows: S1. Sodium hydroxide, sodium sulfate and deionized water are mixed in a mass ratio of 1:2:150 and stirred evenly. Then, bamboo powder with a mass of 100 times that of sodium hydroxide is added and stirred evenly. The mixture is heated to 30°C in a water bath and kept at that temperature for 1 hour. After cooling to room temperature, hydrogen peroxide with a mass fraction of 30% and a mass of 0.16 times that of bamboo powder is added. The pH is adjusted to 10.5 with sodium hydroxide. The mixture is heated to 42°C in a water bath and kept at that temperature for 1.5 hours. The mixture is then transferred to an ice bath at 0°C to terminate the reaction. The pH is adjusted to 6.5 with dilute hydrochloric acid and allowed to stand for 10 minutes. The mixture is washed 8 times with deionized water, filtered and dried, and then ground through a 60-80 mesh sieve to obtain activated bamboo powder. The preparation method of S2. sulfonic acid aniline copolymer is as follows: aniline hydrochloric acid solution and ammonium persulfate are mixed at a mass ratio of 4.8:1, stirred evenly, and then an equal volume of 2,4-diaminobenzenesulfonate acid solution is added. The aniline hydrochloric acid solution is prepared by mixing aniline with 1 mol / L hydrochloric acid at a mass ratio of 1.4:25; the 2,4-diaminobenzenesulfonate acid solution is prepared by mixing 2,4-diaminobenzenesulfonic acid with 1 mol / L hydrochloric acid at a mass ratio of 0.82:25. The reaction is continued at room temperature for 24 hours, washed 8 times with deionized water, dried, and ground into powder to obtain the sulfonic acid aniline copolymer. S3. Sodium alginate, deionized water, and sodium periodate were mixed at a mass ratio of 1:5:1.3 and stirred at 60 rpm for 8 hours. The reaction was terminated by adding an equal mass of ethylene glycol to the sodium periodate. The mixture was precipitated with anhydrous ethanol, washed with deionized water, filtered, and dried to obtain polyaldehyde sodium alginate. Polyaldehyde sodium alginate was then mixed with deionized water at a mass ratio of 0.3:50, heated to 400℃, and stirred until dissolved. An 8-fold mass ratio of sulfonic acid aniline copolymer solution was added. The sulfonic acid aniline copolymer solution was composed of sulfonic acid aniline copolymer and 32% hydrochloric acid at a mass ratio of [missing information]. After mixing at a ratio of 1:50 and stirring evenly, the pH was adjusted to 8.0 with sodium hydroxide. After stirring evenly, glacial acetic acid with a mass of 2 times the weight of the sulfonated aniline copolymer was added dropwise at a rate of 1 ml / min. The pH was then adjusted to 4.5 with sodium acetate, the temperature was raised to 60℃, and the reaction was carried out for 4 hours. Then, activated bamboo powder with a mass of 0.4 times the weight of the sulfonated aniline copolymer was added, and the mixture was stirred at 100 rpm and kept at the temperature for 2 hours. Then, anhydrous ethanol with a mass of 20 times the weight of the sulfonated aniline copolymer was added, stirred, and allowed to stand for 20 minutes. The mixture was then filtered, washed three times with anhydrous ethanol, and dried to obtain sodium alginate sulfonate bamboo powder. S4. 4-Dimethylaminopyridine, N,N-dimethylglycine and dichloromethane were mixed in a mass ratio of 0.09:3:400 and placed in an ice bath at 0℃. After stirring evenly, a 6% dichloromethane solution of 2-chloroethyl isocyanate, 50 times the mass of N,N-dimethylglycine, was added dropwise at a rate of 1 ml / min. The mixture was transferred to room temperature and reacted for 12 h. Then, potassium tert-butoxide, 3.2 times the mass of N,N-dimethylglycine, was added and the reaction was continued for 12 h. The mixture was extracted with dichloromethane, washed with saturated brine, dried over anhydrous magnesium sulfate, and concentrated under reduced pressure to obtain N,N-dimethyl-2-oxazoline. S5. Mix hydrosilicone oil, anhydrous toluene, 4Å molecular sieve, and Karstedt catalyst in a mass ratio of 30:80:3:0.025, stir until homogeneous, heat to 70°C, add 0.3 times the mass of the hydrosilicone oil and a toluene solution of 16% allyl glycidyl ether, maintain the temperature for 2 hours, cool to 60°C, add 0.24 times the mass of the hydrosilicone oil and a toluene solution of 12% allyl alcohol, heat to 70°C again, react for 3 hours, cool and quench with saturated sodium bicarbonate solution, filter, rotary evaporate, precipitate with n-hexane and isopropanol in a volume ratio of 3:1, then add 2 times the mass of the hydrosilicone oil and 0 times the mass of the hydrosilicone oil. 0.1 times the mass of succinic anhydride was heated to 80°C under a nitrogen atmosphere and refluxed for 4 hours. After cooling to room temperature, the mixture was washed with saturated sodium bicarbonate solution, dried with anhydrous sodium sulfate, rotary evaporated, and precipitated again with n-hexane to obtain epoxy-terminated and carboxyl-terminated polydimethylsiloxane. Under a nitrogen atmosphere, epoxy-terminated and carboxyl-terminated polydimethylsiloxane, anhydrous toluene, and tetrabutyl titanate catalyst were mixed in a mass ratio of 10:8:0.01, heated to 110°C, and 0.2 times the mass of N,N-dimethyl-2-oxazoline was added. The mixture was kept at this temperature for 6 hours, cooled to 60°C, distilled under reduced pressure, precipitated with n-hexane, and finally dried to obtain oxazoline polydimethylsiloxane. S6. Oxazoline polydimethylsiloxane, PET, and antioxidant 1010 are mixed at a mass ratio of 1:90:0.1 and extruded using a twin-screw extruder. During extrusion, the feeding zone temperature is 200℃, the melting zone temperature is 245℃, the mixing zone temperature is 260℃, the metering zone temperature is 260℃, the screw speed is 40 rpm, the residence time is 3 min, and finally, the product is water-cooled, air-dried, and pelletized to obtain extended-chain PET. PET, extended-chain PET, and antioxidant 1010 are mixed at a mass ratio of 500:1:0.5 and melt-spun to obtain composite short fibers. S7. Bamboo powder and 5% hydrochloric acid were mixed at a mass ratio of 1:3, stirred at 80 rpm for 2 hours, filtered, washed 8 times with deionized water and dried to obtain acid-washed bamboo powder; the acid-washed bamboo powder was heated to 500℃ at 5℃ / min under a nitrogen atmosphere and kept at that temperature for 2 hours, then pulverized to obtain powder with a median particle size of 2μm; the powder was mixed with potassium hydroxide at a mass ratio of 1:2, activated at 800℃ for 1 hour, washed 8 times with deionized water, rinsed with 30% nitric acid, dried at 100℃, transferred to a plasma treatment instrument, and plasma treated for 3 minutes in an oxygen atmosphere at a power of 60W, then transferred to a dryer for drying to obtain bamboo-based hard carbon material; S8. By mass fraction, lead powder, bamboo-based hard carbon material, sodium alginate bamboo powder, barium sulfate, humic acid, sodium lignin sulfonate, and composite short fibers are mixed and added into a paste mixer. The mixture is stirred for 8 minutes, pure water is added, and stirring is continued for 5 minutes. The temperature is raised to 52°C, kept at the temperature, and dilute sulfuric acid is added dropwise at a rate of 1 ml / min. The temperature is lowered to 40°C by passing cooling water through the mixer, and the density is adjusted to 4.2 g / cm³ to obtain lead paste. The lead paste is coated onto the grid, heated to 45°C, and cured at a relative humidity of 95% for 8 hours. Then, the temperature is raised to 60°C, and the relative humidity is 50% for 10 hours. After drying, the negative electrode formula for lead-acid batteries using bamboo-based hard carbon material is obtained. Example 2
[0024] In this embodiment, the components and weight proportions of the lead-acid battery negative electrode formulation made of bamboo-based hard carbon material are as follows: 100 parts lead powder, 0.9 parts bamboo-based hard carbon material, 0.6 parts sodium alginate sulfonate bamboo powder, 0.8 parts barium sulfate, 0.5 parts humic acid, 0.3 parts sodium lignin sulfonate, 0.1 parts composite short fiber, 10 parts dilute sulfuric acid with a density of 1.1 g / cm³, and 3 parts pure water.
[0025] In this embodiment, the preparation method of the lead-acid battery negative electrode formulation using bamboo-based hard carbon material is as follows: S1. Sodium hydroxide, sodium sulfate, and deionized water are mixed in a mass ratio of 1:2:150 and stirred until homogeneous. Then, bamboo powder with a mass ratio of 110 times that of sodium hydroxide is added and stirred until homogeneous. The mixture is heated in a water bath to 31°C and kept at that temperature for 1 hour. After cooling to room temperature, hydrogen peroxide with a mass fraction of 30% and a mass ratio of 0.16 to 0.18 times that of bamboo powder is added. The pH is adjusted to 10.8 with sodium hydroxide. The mixture is heated in a water bath to 43°C and kept at that temperature for 1.5 hours. The mixture is then transferred to an ice bath at 2°C to terminate the reaction. The pH is adjusted to 6.4 with dilute hydrochloric acid and allowed to stand for 10 to 20 minutes. The mixture is washed 9 times with deionized water, filtered, dried, and ground through a 70-mesh sieve to obtain activated bamboo powder. The preparation method of S2. sulfonic acid aniline copolymer is as follows: aniline hydrochloric acid solution and ammonium persulfate are mixed at a mass ratio of 4.9:1, stirred evenly, and then an equal volume of 2,4-diaminobenzenesulfonate acid solution is added. The aniline hydrochloric acid solution is prepared by mixing aniline with 1 mol / L hydrochloric acid at a mass ratio of 1.45:25; the 2,4-diaminobenzenesulfonate acid solution is prepared by mixing 2,4-diaminobenzenesulfonic acid with 1 mol / L hydrochloric acid at a mass ratio of 0.84:25. The reaction is continued at room temperature for 26 hours, washed 9 times with deionized water, dried, and ground into powder to obtain the sulfonic acid aniline copolymer. S3. Sodium alginate, deionized water, and sodium periodate were mixed in a mass ratio of 1.05:5:1.4 and stirred at 70 rpm for 10 hours. The reaction was terminated by adding an equal mass of ethylene glycol to the sodium periodate. The mixture was precipitated with anhydrous ethanol, washed with deionized water, filtered, and dried to obtain polyaldehyde sodium alginate. Polyaldehyde sodium alginate was then mixed with deionized water in a mass ratio of 0.4:50, heated to 45°C, and stirred until dissolved. A sulfonic acid aniline copolymer solution, consisting of sulfonic acid aniline copolymer and 34% hydrochloric acid, was added in a mass ratio of 9:1.4. After mixing at a ratio of 1:50 and stirring evenly, the pH was adjusted to 8.5 with sodium hydroxide. After stirring evenly, 2.5 times the mass of sulfonated aniline copolymer in glacial acetic acid was added dropwise at a rate of 2 ml / min. The pH was then adjusted to 5.0 with sodium acetate, and the temperature was raised to 61℃. The reaction was carried out for 5 h. Then, 0.5 times the mass of sulfonated aniline copolymer in activated bamboo powder was added. The mixture was stirred at 150 rpm and kept at the temperature for 2.5 h. Then, 30 times the mass of sulfonated aniline copolymer in anhydrous ethanol was added. After stirring, the mixture was allowed to stand for 25 min, filtered, washed 4 times with anhydrous ethanol, and dried to obtain sodium alginate sulfonate bamboo powder. S4. 4-Dimethylaminopyridine, N,N-dimethylglycine and dichloromethane were mixed in a mass ratio of 0.1:3:450 and placed in an ice bath at 4°C. After stirring evenly, a 7% dichloromethane solution of 2-chloroethyl isocyanate, 55 times the mass of N,N-dimethylglycine, was added dropwise at a rate of 2 ml / min. The mixture was then transferred to room temperature and reacted for 13 h. Potassium tert-butoxide, 3.4 times the mass of N,N-dimethylglycine, was added, and the reaction was continued for another 13 h. The mixture was then extracted with dichloromethane, washed with saturated brine, dried over anhydrous magnesium sulfate, and concentrated under reduced pressure to obtain N,N-dimethyl-2-oxazoline. S5. Mix hydrosilicone oil, anhydrous toluene, 4Å molecular sieve, and Karstedt catalyst in a mass ratio of 40:80:3:0.025, stir until homogeneous, heat to 71°C, add 0.35 times the mass of the hydrosilicone oil in a 17% allyl glycidyl ether toluene solution, maintain the reaction temperature for 2.5 h, cool to 61°C, add 0.25 times the mass of the hydrosilicone oil in a 13% allyl alcohol toluene solution, heat again to 71°C, react for 3.5 h, cool and quench with saturated sodium bicarbonate solution, filter, rotary evaporate, precipitate with a 3:1 volume ratio of n-hexane and isopropanol, then add 2.1 times the mass of the hydrosilicone oil in anhydrous toluene and a 17% allyl glycidyl ether toluene solution. Succinic anhydride in an amount of 0.15 times was heated to 83°C and refluxed for 5 hours under a nitrogen atmosphere. After cooling to room temperature, it was washed with saturated sodium bicarbonate solution, dried with anhydrous sodium sulfate, rotary evaporated, and precipitated again with n-hexane to obtain epoxy- and carboxyl-terminated polydimethylsiloxane. Under a nitrogen atmosphere, epoxy- and carboxyl-terminated polydimethylsiloxane, anhydrous toluene, and tetrabutyl titanate catalyst were mixed in a mass ratio of 10:8:0.015, heated to 115°C, and N,N-dimethyl-2-oxazoline in an amount of 0.21 times the mass of epoxy- and carboxyl-terminated polydimethylsiloxane was added. The mixture was kept at this temperature for 7 hours, cooled to 61°C, distilled under reduced pressure, precipitated with n-hexane, and finally dried to obtain oxazoline polydimethylsiloxane. S6. Oxazoline polydimethylsiloxane, PET, and antioxidant 1010 are mixed at a mass ratio of 1:95:0.1 and extruded using a twin-screw extruder. During extrusion, the feeding zone temperature is 210℃, the melting zone temperature is 250℃, the mixing zone temperature is 264℃, the metering zone temperature is 261℃, the screw speed is 50 rpm, and the residence time is 4 min. Finally, the mixture is water-cooled, air-dried, and pelletized to obtain extended-chain PET. PET, extended-chain PET, and antioxidant 1010 are mixed at a mass ratio of 500:1.5:0.5 and melt-spun to obtain composite short fibers. S7. Bamboo powder and 5% hydrochloric acid were mixed at a mass ratio of 1:3, stirred at 900 rpm for 3 hours, filtered, washed 9 times with deionized water and dried to obtain acid-washed bamboo powder; the acid-washed bamboo powder was heated to 600℃ at 8℃ / min under a nitrogen atmosphere and kept at that temperature for 3 hours, then pulverized to obtain powder with a median particle size of 6μm; the powder was mixed with potassium hydroxide at a mass ratio of 1:3, activated at 900℃ for 1.5 hours, washed 9 times with deionized water, rinsed with 31% nitric acid, dried at 105℃, transferred to a plasma treatment instrument, and plasma treated for 4 minutes at 70W in an oxygen atmosphere, then transferred to a dryer for drying to obtain bamboo-based hard carbon material; S8. By mass fraction, lead powder, bamboo-based hard carbon material, sodium alginate bamboo powder sulfonate, barium sulfate, humic acid, sodium lignin sulfonate, and composite short fibers are mixed and added into a paste mixer. The mixture is stirred for 12 minutes, pure water is added, and stirring is continued for 8 minutes. The temperature is raised to 56°C, kept at the temperature, and dilute sulfuric acid is added dropwise at a rate of 2 ml / min. The temperature is lowered to 41°C by passing cooling water through the mixer, and the density is adjusted to 4.4 g / cm³ to obtain lead paste. The lead paste is coated on the grid, heated to 48°C, and cured at a relative humidity of 95% for 10 hours. Then, the temperature is raised to 63°C, and the relative humidity is 50% for 13 hours. After drying, the negative electrode formula for lead-acid batteries using bamboo-based hard carbon material is obtained. Example 3
[0026] In this embodiment, the components and weight proportions of the lead-acid battery negative electrode formulation made of bamboo-based hard carbon material are as follows: 100 parts lead powder, 1.5 parts bamboo-based hard carbon material, 0.8 parts sodium alginate sulfonate bamboo powder, 1.2 parts barium sulfate, 0.8 parts humic acid, 0.5 parts sodium lignin sulfonate, 0.15 parts composite short fiber, 12 parts dilute sulfuric acid with a density of 1.20 g / cm³, and 15 parts pure water.
[0027] In this embodiment, the preparation method of the lead-acid battery negative electrode formulation using bamboo-based hard carbon material is as follows: S1. Sodium hydroxide, sodium sulfate, and deionized water are mixed in a mass ratio of 1:2:150 and stirred evenly. Then, bamboo powder with a mass of 120 times that of sodium hydroxide is added and stirred evenly. The mixture is heated to 32°C in a water bath and kept at that temperature for 1.5 hours. After cooling to room temperature, hydrogen peroxide with a mass fraction of 30% and a mass of 0.18 times that of bamboo powder is added. The pH is adjusted to 11.0 with sodium hydroxide. The mixture is heated to 45°C in a water bath and kept at that temperature for 2 hours. The reaction is then terminated by transferring the mixture to an ice bath at 3°C. The pH is adjusted to 7.0 with dilute hydrochloric acid and allowed to stand for 20 minutes. The mixture is washed 10 times with deionized water, filtered, dried, and ground through an 80-mesh sieve to obtain activated bamboo powder. The preparation method of S2. sulfonic acid aniline copolymer is as follows: aniline hydrochloric acid solution and ammonium persulfate are mixed at a mass ratio of 5.2:1, stirred evenly, and then an equal volume of 2,4-diaminobenzenesulfonate acid solution is added. The aniline hydrochloric acid solution is prepared by mixing aniline with 1 mol / L hydrochloric acid at a mass ratio of 1.5:25; the 2,4-diaminobenzenesulfonate acid solution is prepared by mixing 2,4-diaminobenzenesulfonic acid with 1 mol / L hydrochloric acid at a mass ratio of 0.86:25. The reaction is continued at room temperature for 28 hours, washed 10 times with deionized water, dried, and ground into powder to obtain the sulfonic acid aniline copolymer. S3. Sodium alginate, deionized water, and sodium periodate were mixed in a mass ratio of 1.1:5:1.5 and stirred at 80 rpm for 12 hours. The reaction was terminated by adding an equal mass of ethylene glycol to the sodium periodate. The mixture was precipitated with anhydrous ethanol, washed with deionized water, filtered, and dried to obtain polyaldehyde sodium alginate. Polyaldehyde sodium alginate was then mixed with deionized water in a mass ratio of 0.5:50, heated to 50°C, and stirred until dissolved. A sulfonic acid aniline copolymer solution, consisting of sulfonic acid aniline copolymer and 36% hydrochloric acid, was added in a mass ratio of 10 times the mass of the polyaldehyde sodium alginate. After mixing in a ratio of 1:50 and stirring evenly, the pH was adjusted to 9.0 with sodium hydroxide. After stirring evenly, glacial acetic acid with a mass of 3 times the weight of the sulfonated aniline copolymer was added dropwise at a rate of 3 ml / min. The pH was then adjusted to 5.5 with sodium acetate, the temperature was raised to 62℃, and the reaction was carried out for 6 hours. Then, activated bamboo powder with a mass of 0.6 times the weight of the sulfonated aniline copolymer was added, and the mixture was stirred and kept at the temperature for 3 hours. Then, anhydrous ethanol with a mass of 40 times the weight of the sulfonated aniline copolymer was added, stirred, and allowed to stand for 30 minutes. The mixture was then filtered, washed 5 times with anhydrous ethanol, and dried to obtain sodium alginate sulfonate bamboo powder. S4. 4-Dimethylaminopyridine, N,N-dimethylglycine and dichloromethane were mixed in a mass ratio of 0.12:3:500 and placed in an ice bath at 3°C. After stirring evenly, a dichloromethane solution of 8% 2-chloroethyl isocyanate, which was 60 times the mass of N,N-dimethylglycine, was added dropwise at a rate of 3 ml / min. The mixture was transferred to room temperature and reacted for 14 h. Then, potassium tert-butoxide, which was 2.5 times the mass of N,N-dimethylglycine, was added and the reaction was continued for 14 h. The mixture was extracted with dichloromethane, washed with saturated brine, dried over anhydrous magnesium sulfate, and concentrated under reduced pressure to obtain N,N-dimethyl-2-oxazoline. S5. Mix hydrosilicone oil, anhydrous toluene, 4Å molecular sieve, and Karstedt catalyst in a mass ratio of 50:80:3:0.025, stir until homogeneous, heat to 72°C, add 0.4 times the mass of the hydrosilicone oil and a toluene solution containing 18% allyl glycidyl ether, maintain the reaction temperature for 3 hours, cool to 62°C, add 0.26 times the mass of the hydrosilicone oil and a toluene solution containing 14% allyl alcohol, heat to 72°C again, react for 4 hours, cool and quench with saturated sodium bicarbonate solution, filter, rotary evaporate, precipitate with a 3:1 volume ratio of n-hexane and isopropanol, then add 2.2 times the mass of the hydrosilicone oil and 0. 0.2 times the mass of succinic anhydride was heated to 85°C and refluxed for 6 hours under a nitrogen atmosphere. After cooling to room temperature, the mixture was washed with saturated sodium bicarbonate solution, dried with anhydrous sodium sulfate, rotary evaporated, and precipitated again with n-hexane to obtain epoxy- and carboxyl-terminated polydimethylsiloxane. Under a nitrogen atmosphere, epoxy- and carboxyl-terminated polydimethylsiloxane, anhydrous toluene, and tetrabutyl titanate catalyst were mixed in a mass ratio of 10:8:0.02, heated to 120°C, and 0.22 times the mass of N,N-dimethyl-2-oxazoline was added. The mixture was kept at this temperature for 8 hours, cooled to 62°C, distilled under reduced pressure, precipitated with n-hexane, and finally dried to obtain oxazoline polydimethylsiloxane. S6. Oxazoline polydimethylsiloxane, PET, and antioxidant 1010 are mixed at a mass ratio of 1:100:0.1 and extruded using a twin-screw extruder. During extrusion, the feeding zone temperature is 220℃, the melting zone temperature is 255℃, the mixing zone temperature is 268℃, the metering zone temperature is 262℃, the screw speed is 60 rpm, and the residence time is 5 min. Finally, the mixture is water-cooled, air-dried, and pelletized to obtain extended-chain PET. PET, extended-chain PET, and antioxidant 1010 are mixed at a mass ratio of 500:2:0.5 and melt-spun to obtain composite short fibers. S7. Bamboo powder and 5% hydrochloric acid were mixed at a mass ratio of 1:3, stirred at 100 rpm for 4 hours, filtered, washed 10 times with deionized water and dried to obtain acid-washed bamboo powder; the acid-washed bamboo powder was heated to 700℃ at 10℃ / min under a nitrogen atmosphere and kept at the temperature for 4 hours, then pulverized to obtain powder with a median particle size of 8μm; the powder was mixed with potassium hydroxide at a mass ratio of 1:4, activated at 1000℃ for 2 hours, washed 10 times with deionized water, rinsed with 32% nitric acid, dried at 110℃, transferred to a plasma treatment instrument, and plasma treated for 5 minutes at 80W in an oxygen atmosphere, and then transferred to a dryer to dry to obtain bamboo-based hard carbon material; S8. By mass fraction, lead powder, bamboo-based hard carbon material, sodium alginate bamboo powder, barium sulfate, humic acid, sodium lignin sulfonate, and composite short fibers are mixed and added into a paste mixer. The mixture is stirred for 15 minutes, pure water is added, and stirring is continued for 10 minutes. The temperature is raised to 58°C, kept at the temperature, and dilute sulfuric acid is added dropwise at a rate of 5 ml / min. The temperature is lowered to 42°C by passing cooling water through the mixer, and the density is adjusted to 4.5 g / cm³ to obtain lead paste. The lead paste is coated onto the grid, heated to 50°C, and cured at a relative humidity of 95% for 12 hours. Then, the temperature is raised to 65°C, and the relative humidity is 50% for 15 hours. The mixture is then dried to obtain the lead-acid battery negative electrode formula of bamboo-based hard carbon material.
[0028] Comparative Example 1 The preparation method of Comparative Example 1 is the same as that of Example 2. The difference between the negative electrode formulation of this bamboo-based hard carbon material lead-acid battery and that of Example 2 is that the negative electrode formulation only includes lead powder, bamboo-based hard carbon material, barium sulfate, humic acid, sodium lignosulfonate, composite short fibers, dilute sulfuric acid and pure water.
[0029] Comparative Example 2 The preparation method of Comparative Example 2 is the same as that of Example 2. The difference between the negative electrode formulation of this bamboo-based hard carbon material lead-acid battery and that of Example 2 is that the negative electrode formulation only includes lead powder, bamboo-based hard carbon material, sodium alginate sulfonate bamboo powder, barium sulfate, humic acid, sodium lignin sulfonate, dilute sulfuric acid and pure water.
[0030] Comparative Example 3 The preparation method of Comparative Example 3 is the same as that of Example 2. The difference between the negative electrode formulation of this bamboo-based hard carbon material lead-acid battery and that of Example 2 is that the negative electrode formulation only includes lead powder, bamboo-based hard carbon material, barium sulfate, humic acid, sodium lignosulfonate, dilute sulfuric acid and pure water.
[0031] Example of effect The test results of the examples and comparative examples are shown in Table 1; Table 1
[0032] As can be seen from the performance data comparison in Table 1 and the accompanying drawings, the bamboo-based hard carbon material lead-acid battery negative electrode formulation prepared by the present invention has high capacity retention rate and high utilization rate of negative electrode active material. Comparison of experimental data from Examples 1, 2, and 3 and Comparative Examples 1, 2, and 3 reveals that the formation of a triple anchoring network in the lead paste effectively inhibits the volume expansion and peeling of the active material during charge and discharge, improving cycle life while significantly enhancing capacity retention. Furthermore, during the curing and drying stage, the network reacts with the alkaline components in the lead paste, partially transforming into insoluble lead alginate gel, further anchoring bamboo powder within the active material skeleton and preventing bamboo powder agglomeration from affecting the uniformity of the negative electrode plate. The introduction of oxazoline into the composite short fibers allows for coordination adsorption with the negative electrode active material and interfacial interaction with the sodium alginate carboxyl groups. The polydimethylsiloxane segments reduce fiber surface energy, improving the wetting and dispersibility of the lead paste and significantly enhancing the binding force of the negative electrode active material. This improves both the deep cycle life of the battery and the utilization rate of the negative electrode active material.
[0033] Obviously, the above embodiments are merely examples to clearly illustrate the embodiments of the present invention, and are not intended to limit the embodiments of the present invention. Those skilled in the art can make other variations or modifications based on the above description. It is neither necessary nor possible to exhaustively list all embodiments here. However, these obvious variations or modifications derived from the spirit of the present invention are still within the protection scope of the present invention.
Claims
1. A lead paste for the negative electrode of a lead-acid battery made of bamboo-based hard carbon material, characterized in that, The raw materials include the following parts by weight: 100 parts lead powder, 0.2-1.5 parts bamboo-based hard carbon material, 0.2-0.8 parts sodium alginate sulfonate bamboo powder, 0.5-1.2 parts barium sulfate, 0.2-0.8 parts humic acid, 0.1-0.5 parts sodium lignin sulfonate, 0.05-0.15 parts composite short fibers, and 8-12 parts of a material with a density of 1.05-1.
20. The mixture consists of g / cm³ of dilute sulfuric acid and 10-15 parts of pure water; the sodium alginate bamboo powder is prepared by reacting sulfonic acid-based aniline copolymer with polyaldehyde sodium alginate, and then reacting it with activated bamboo powder; the composite short fiber is prepared by melt spinning oxazoline polydimethylsiloxane with polyethylene terephthalate; the oxazoline polydimethylsiloxane is prepared by reacting N,N-dimethyl-2-oxazoline with terminal epoxy and terminal carboxyl polydimethylsiloxane.
2. A method for preparing a negative electrode of a lead-acid battery using bamboo-based hard carbon material, wherein the lead paste for the negative electrode is the lead paste as described in claim 1, characterized in that... The specific steps include the following: S1. Mix sodium hydroxide, sodium sulfate, and deionized water in a mass ratio of 1:2:
150. After stirring evenly, add bamboo powder at a mass ratio of 100-120 times that of sodium hydroxide. Stir evenly, heat the mixture in a water bath to 30-32°C, keep it at that temperature for 1-1.5 hours, cool it to room temperature, add hydrogen peroxide at a mass fraction of 30% at a mass ratio of 0.16-0.18 times that of bamboo powder, adjust the pH to 10.5-11.0 with sodium hydroxide, heat the mixture in a water bath to 42-45°C, keep it at that temperature for 1.5-2 hours, transfer it to an ice bath at 0-3°C to terminate the reaction, adjust the pH to 6.5-7.0 with dilute hydrochloric acid, let it stand for 10-20 minutes, wash it 8-10 times with deionized water, filter and dry it, grind it through a 60-80 mesh sieve to obtain activated bamboo powder. The preparation method of S2. sulfonic acid aniline copolymer is as follows: aniline hydrochloric acid solution and ammonium persulfate are mixed at a mass ratio of 4.8~5.2:1, stirred evenly, and then an equal volume of 2,4-diaminobenzenesulfonate acid solution is added. The reaction is continued at room temperature for 24~28 hours. The mixture is washed 8~10 times with deionized water, dried, and ground into powder to obtain sulfonic acid aniline copolymer. S3. Mix sodium polyaldehyde alginate with deionized water at a mass ratio of 0.3~0.5:50, heat to 40~50℃, stir to dissolve, then add 8~10 times the mass of sodium polyaldehyde alginate solution of sulfonic acid aniline copolymer. The sulfonic acid aniline copolymer solution is prepared by mixing sulfonic acid aniline copolymer with 32~36% hydrochloric acid at a mass ratio of 1:50, stirring until homogeneous, and then adjusting the pH to 8.0~9.0 with sodium hydroxide. After stirring until homogeneous, add sulfonic acid aniline copolymer dropwise at a rate of 1~3 ml / min. Add 2-3 times the mass of acetic acid to the sulfonic acid aniline copolymer, adjust the pH to 4.5-5.5 with sodium acetate, heat to 60-62℃, and react for 4-6 hours. Then add 0.4-0.6 times the mass of activated bamboo powder to the sulfonic acid aniline copolymer, stir and keep warm at 100-200 rpm for 2-3 hours, add 20-40 times the mass of anhydrous ethanol to the sulfonic acid aniline copolymer, stir, let stand for 20-30 minutes, filter, wash 3-5 times with anhydrous ethanol, and dry to obtain sodium alginate sulfonate bamboo powder. S4. Mix 4-dimethylaminopyridine, N,N-dimethylglycine, and dichloromethane in a mass ratio of 0.09~0.12:3:400~500, place in an ice bath at 0~3℃, stir until homogeneous, then add dropwise a 6~8% (50~60 times) dichloromethane solution of 2-chloroethyl isocyanate (by mass) of N,N-dimethylglycine at a rate of 1~3 ml / min. Transfer to room temperature and react for 12~14 h. Then add potassium tert-butoxide (3.2~3.5 times) potassium tert-butoxide (by mass) of N,N-dimethylglycine, and continue the reaction for 12~14 h. Extract with dichloromethane, wash with saturated brine, dry with anhydrous magnesium sulfate, and concentrate under reduced pressure to obtain N,N-dimethyl-2-oxazoline. S5. Under a nitrogen atmosphere, epoxy-terminated and carboxyl-terminated polydimethylsiloxane, anhydrous toluene, and tetrabutyl titanate catalyst were mixed in a mass ratio of 10:8:0.01~0.
02. The mixture was heated to 110~120℃, and N,N-dimethyl-2-oxazoline was added at 0.2~0.22 times the mass of the epoxy-terminated and carboxyl-terminated polydimethylsiloxane. The mixture was kept at this temperature for 6~8 hours, cooled to 60~62℃, and distilled under reduced pressure. The mixture was precipitated with n-hexane and finally dried to obtain oxazoline polydimethylsiloxane. S6. Oxazoline polydimethylsiloxane, PET and antioxidant 1010 are mixed at a mass ratio of 1:90~100:0.1 and extruded using a twin-screw extruder to obtain extended chain PET; PET, extended chain PET and antioxidant 1010 are mixed at a mass ratio of 500:1~2:0.5 and melt-spun to obtain composite short fibers; S7. By mass fraction, lead powder, bamboo-based hard carbon material, sodium alginate bamboo powder, barium sulfate, humic acid, sodium lignin sulfonate, and composite short fibers are mixed and added into a paste mixer. The mixture is stirred for 8-15 minutes, pure water is added, and stirring is continued for 5-10 minutes. The temperature is raised to 52-58℃, kept at the temperature, and dilute sulfuric acid is added dropwise at a rate of 1-5 ml / min. The temperature is lowered to 40-42℃ by circulating cooling water, and the density is adjusted to 4.2-4.5 g / cm³ to obtain lead paste. The lead paste is coated onto the grid, heated to 45-50℃, and cured at a relative humidity of 95% for 8-12 hours. Then, the temperature is raised to 60-65℃, and the relative humidity is 50% for 10-15 hours. The mixture is then dried to obtain the negative electrode of a lead-acid battery made of bamboo-based hard carbon material.
3. The method for preparing a lead-acid battery negative electrode made of bamboo-based hard carbon material according to claim 2, characterized in that, In step S2 above, the aniline hydrochloric acid solution is prepared by mixing aniline with 1 mol / L hydrochloric acid at a mass ratio of 1.4~1.5:25; the 2,4-diaminobenzenesulfonic acid solution is prepared by mixing 2,4-diaminobenzenesulfonic acid with 1 mol / L hydrochloric acid at a mass ratio of 0.82~0.86:
25.
4. The method for preparing a lead-acid battery negative electrode made of bamboo-based hard carbon material according to claim 2, characterized in that, In step S3 above, the preparation method of polyaldehyde sodium alginate is as follows: sodium alginate, deionized water and sodium periodate are mixed in a mass ratio of 1~1.1:5:1.3~1.5, stirred at 60~80 rpm for 8~12 h, the reaction is terminated by adding an equal mass of ethylene glycol to sodium periodate, precipitated with anhydrous ethanol, washed with deionized water, filtered and dried to obtain polyaldehyde sodium alginate.
5. The method for preparing a lead-acid battery negative electrode made of bamboo-based hard carbon material according to claim 2, characterized in that, In step S5 above, the preparation method of the epoxy-terminated and carboxyl-terminated polydimethylsiloxane is as follows: Hydrogen-containing silicone oil, anhydrous toluene, 4Å molecular sieve, and Karstedt catalyst are mixed in a mass ratio of 30-50:80:3:0.025, stirred evenly, heated to 70-72℃, and 0.3-0.4 times the mass of the hydrogen-containing silicone oil (16-18% by mass) of an allyl glycidyl ether toluene solution is added. The reaction is maintained at this temperature for 2-3 hours, then cooled to 60-62℃, and 0.24-0.26 times the mass of the hydrogen-containing silicone oil (12-14% by mass) of an allyl glycidyl ether toluene solution is added. A toluene solution of allyl alcohol is heated to 70-72°C and reacted for 3-4 hours. After cooling and quenching with saturated sodium bicarbonate solution, the mixture is filtered, rotary evaporated, and precipitated with hexane and isopropanol in a volume ratio of 3:
1. Then, anhydrous toluene (2-2.2 times the mass of the hydrogen-containing silicone oil) and succinic anhydride (0.1-0.2 times the mass of the hydrogen-containing silicone oil) are added. Under a nitrogen atmosphere, the mixture is heated to 80-85°C and refluxed for 4-6 hours. After cooling to room temperature, the mixture is washed with saturated sodium bicarbonate solution, dried with anhydrous sodium sulfate, rotary evaporated, and precipitated again with hexane to obtain epoxy-terminated and carboxyl-terminated polydimethylsiloxane.
6. The method for preparing a lead-acid battery negative electrode made of bamboo-based hard carbon material according to claim 2, characterized in that, In step S6 above, during extrusion by the twin-screw extruder, the temperature of the feeding zone is 200~220℃, the temperature of the melting zone is 245~255℃, the temperature of the mixing zone is 260~268℃, the temperature of the metering zone is 260~262℃, the screw speed is 40~60 rpm, the residence time is 3~5 min, and finally the extruder is water-cooled, air-dried, and pelletized.
7. The method for preparing a lead-acid battery negative electrode made of bamboo-based hard carbon material according to claim 2, characterized in that, In step S7 above, the preparation method of bamboo-based hard carbon material is as follows: bamboo powder is mixed with 5% hydrochloric acid at a mass ratio of 1:3, stirred at 80-100 rpm for 2-4 hours, filtered, washed with deionized water 8-10 times and dried to obtain acid-washed bamboo powder; the acid-washed bamboo powder is heated to 500-700℃ at 5-10℃ / min under a nitrogen atmosphere and kept at the temperature for 2-4 hours, pulverized to obtain powder with a median particle size of 2-8μm, the powder is mixed with potassium hydroxide at a mass ratio of 1:2-4, activated at 800-1000℃ for 1-2 hours, washed with deionized water 8-10 times, rinsed with 30-32% nitric acid, dried at 100-110℃, transferred to a plasma treatment instrument, and plasma treated for 3-5 minutes in an oxygen atmosphere at a power of 60-80W, and then transferred to a dryer for drying to obtain bamboo-based hard carbon material.
Citation Information
Patent Citations
Lead-acid storage battery with high energy storage capacity and long service life
CN104241708A
Cathode, anode and electrolyte formula for solar power generation storage battery and preparation method of cathode, anode and electrolyte formula
CN106711405A